До проблеми визначення поняття «адміністративно-правова охорона та захист відбору осіб на службу в Національну поліцію України» - Гарбузюк, К. Г.; Harbuziuk, K. H.; ORCID: http://orcid.org/0000-0002-6714-5074 (Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 2. - С. 36-40, 2019)
Запропоновано авторське визначення поняття «адміністративно-правова охорона та захист відбору осіб на службу в Національну поліцію України». З’ясовано, що об’єктом адміністративно-правової охорони відбору осіб, які уперше приймаються на службу в Національну поліцію України , є суспільні відносини з приводу реалізації громадянами України права бути прийнятими на службу в поліцію на конкурсній основі та діяльності державних інституцій, що провадять відбір. Охорона цих відносин відображена у нормативно-правових актах у формі: заборон, приписів, санкцій тощо, які мають на меті уникнення негативних станів, як права бути прийнятими на службу в поліцію, так і виконання обов’язків із проведення конкурсу. Встановлено, що чинне законодавство передбачає шляхи захисту кандидатом своїх прав – звернення до адміністративного суду або/та до вищого органу або посадової особи, а також розгляд суті скарги в суді чи керівництвом, включно з перевіркою під час дисциплінарного провадження.

The purpose of the article is to provide the author’s definition of the concept of administrative and legal protection and protection of the selection of persons for service in the National Police of Ukraine. Thus, in the article, based on the analysis of scientific views of scientists and norms of the current legislation of Ukraine, the author defines the concept of administrative and legal protection and protection of the selection of persons for service in the National Police of Ukraine. It has been found out that the object of administrative and legal protection for the selection of first-time recruiters in the NPS is public relations regarding the realization by citizens of Ukraine of the right to be admitted to the police on a competitive basis and the activities of the state institutions that carry out the selection. The protection of these relations is reflected in the legal acts in the form of prohibitions, prescriptions, sanctions, etc., aimed at avoiding negative conditions, as the right to be admitted to the police service and to perform the duties of conducting the competition. It is determined that under the administrative and legal protection of the selection of persons who are first enlisted in the NPS, we propose to understand the consolidation in normative legal acts of the norms of the law directed in the sphere of selection to the police for the prevention of negative: including the prevention of offenses, incl. misconduct; preservation of conditions of behavior of participants of legal relations; restoration and elimination of obstacles in the exercise of the right to be admitted to the NPS and fulfillment of the competition responsibilities by authorized state institutions. It is established that the current legislation provides for ways of protecting a candidate’s rights by applying to an administrative court or/and a higher body or official, as well as to reviewing the merits of a complaint in a court or management, including review during disciplinary proceedings. Thus, under the administrative and legal protection of the selection of first-time enrollees in the NPS, we understand public relations in restoring the violated right to be employed in the NPS or the obligation to hold a competition by authorized state institutions, as well as removing obstacles in its implementation by means administrative law.

Предложено авторское определение понятия "административно-правовая охрана и защита отбора лиц на службу в Национальную полицию Украины". Выяснено, что объектом административно-правовой охраны отбора лиц, которые впервые принимаются на службу в Национальную полицию Украины, являются общественные отношения по поводу реализации гражданами Украины права быть принятыми на службу в полицию на конкурсной основе и деятельности государственных институтов, осуществляющих отбор. Охрана этих отношений отражена в нормативно-правовых актах в форме: запретов, предписаний, санкций и т.п., которые имеют целью избежать негативных состояний, как права быть принятыми на службу в полицию, так и выполнения обязанностей по проведению конкурса. Установлено, что действующее законодательство предусматривает пути защиты кандидатом своих прав – обращение в административный суд или высший орган, либо к должностному лицу, а также рассмотрение сути жалобы в суде или руководством, включая проверку во время дисциплинарного производства.
Гарбузюк, К. Г. До проблеми визначення поняття «адміністративно-правова охорона та захист відбору осіб на службу в Національну поліцію України» / Гарбузюк К. Г. // Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 2. - С. 36-40. - DOI: https://doi.org/10.32844/2618-1258.2019.4-2.7.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; адміністративно-правова охорона; administrative and legal protection; административно-правовая охрана; адміністративно-правовий захист; administrative and legal protection; административно-правовая защита; відбір осіб; selection of persons; отбор лиц; кандидати; candidates; кандидаты